Production of microalgae-derived exo-polygalacturonase for fruit juice clarification - Uzuner, Sibel; Evrendilek, Gulsun Akdemir; Kurhan, Sebnem (Frontiers in Food Science and Technology, 2022)
Due to growing demand for the commercial enzymes with higher efficacy derived from the renewable and sustainable resources, algal biomass has gained more attention. Thus, production of exo-polygalacturonase (PGase) from Bacillus subtilis under submerged fermentation (SmF) using algal feed stocks as a carbon source in fermentation medium and its potential use for the clarification of apple and carrot juices with the optimization of the enzyme load, pH, and time using Box-Behnken response surface methodology (RSM) were prompted. The maximum PGase activity of 510.61± 7.86 U/L was achieved at pH 5.0 after 48h at 40 oC using 0.5 % (w/v) pectin, 0.1% (w/v) yeast extract, 0.02% (w/v) MgSO47H2O, 0.02% (w/v) K2HPO4, 0.3% (w/v) glucose, and 0.583% (w/v) microalgae hydrolyzate as a the fermentation medium. PGase production without glucose was favoured by SmF with shake flask working volume of 100 mL (248.90± 4.58 U/L) as compared to bioreactor with working volume of 1 L (192.99±0.84) for 48h. Both carrot and apple juices were treated with the crude PGase (248.9 U/L) at different concentrations (0.1-0.5%), temperature (30-50oC), and time (30-120 min) and the maximal clarification conditions were obtained as 0.3% (w/v) enzyme concentration at 50 oC for 30 min exposure time. This study revealed that microalgae-derived PGase in crude form can be effectively used for clarification of the juices.